PHENOTYPIC AND GENETIC DIVERSITY OF ENTEROVIRUSES IN THE REPUBLIC OF BELARUS, 2003-2022 - Paklonskaya, N.V.; Amvrosieva, T.V.; Bogush, Z.F.; Shilova, Yu.A.; Koltunova, Yu.B.; Dashkevich, A.M.; Zapolskaya, V.V.; Kishkurno, E.P. (Eurasian Journal of Applied Biotechnology, 2023)
Enteroviruses (EV) are widespread viral agents that regularly cause epidemic outbreaks of diseases that are characterized by a variety of clinical manifestations. The aim of this work was to study the phenotypic and genotypic diversity of non-poliomyelitis EVs that circulated from 2003 to 2022 in our country during epidemic upsurges and decreases of enteroviral morbidity. It was established that during this period there was a circulation of 44 different types of EVs belonging to the species Enterovirus B (97.8%), Enterovirus A (1.88%), Enterovirus C (0.9%), Enterovirus D (0.4 %). Among Enterovirus B viruses, Coxsackievirus B5, ECHO 30, and ECHO11 prevailed. During the years of epidemic rises of morbidity, the ECHO 30, ECHO 9 and ECHO 11 viruses were significantly more often identified (p< 0.001), while in the years of decreases Coxsackievirus B1, B2, B3 and B4 were detected more often (p< 0.001). ECHO 6 and Coxsackievirus B5 viruses were registered both during periods of epidemic ups and downs and were characterized by the maximum intratype genetic diversity, significantly greater than ECHO30, ECHO6 and ECHO 11 (p< 0.05). During the observation period, 9 genetic variants of ECHO 30, 6 – of ECHO 9, 3 – of ECHO 11, 6 – of ECHO 6 and 13 – of Coxsackievirus B5 were identified. An analysis of the genetic diversity of ECHO 30, 9, 11, 6, Coxsackie B5 viruses showed that the upsurges of enteroviral morbidity was accompanied by the maximum number of detected genetic variants and some of them were new to the country's population. The data obtained indicate the multifactorial nature of the formation of the epidemic process and a significant contribution to its formation of the genetic diversity of pathogens.